1977
DOI: 10.1029/wr013i006p00992
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hysteresis effect on transient flows in saturated‐unsaturated porous media

Abstract: In the following report the authors experimentally and numerically study one-and two-dimensional transient flows where the hysteresis of the relationship of suction-water content clearly appears. In the numerical simulation of these flows, by using a finite element method, the hysteresis effect is taken into account by corlsidering both its primary and secondary scanning curves; when the seepage surface occurs, it too is taken into account. The comparison with experimental results shows that in the concerned p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…In two-phase systems, for example, there is a single capillary pressure PCNW = PN -pw. In simple models PCNW is a function of saturation; however, in actual flows the capillary pressure exhibits rather pronounced hysteresis (103,82,134) and dependence on fluid composition (42). Flow equations for systems having more fluid phases will be similar, except that if P phases coexist, then P -1 independent capillary pressure functions will appear in the system.…”
Section: Review Of the Basic Physicsmentioning
confidence: 99%
“…In two-phase systems, for example, there is a single capillary pressure PCNW = PN -pw. In simple models PCNW is a function of saturation; however, in actual flows the capillary pressure exhibits rather pronounced hysteresis (103,82,134) and dependence on fluid composition (42). Flow equations for systems having more fluid phases will be similar, except that if P phases coexist, then P -1 independent capillary pressure functions will appear in the system.…”
Section: Review Of the Basic Physicsmentioning
confidence: 99%
“…The SWCC is hysteretic, (i.e., the water content at a given suction on a wetting path is less than that on a drying path). Hysteresis in the ψ(θ) relationship has been observed widely for many soil samples in the laboratory (Poulovassilis, 1970a(Poulovassilis, , 1970bHoa et al, 1977;etc.). Cyclic changes often entail wetting and drying scanning curves, which may form loops between two boundary curves.…”
Section: Introductionmentioning
confidence: 96%
“…The second group mainly relies on an analysis of SWCC shape and properties. These empirical models assume that the primary, secondary, and higher-order scanning curves can be scaled from the main boundary curves (Hoa et al, 1977;Scott et al, 1983;Huang et al, 2005). Experimental validation of these models is however, still limited.…”
Section: Introductionmentioning
confidence: 98%
“…Ignoring hysteresis in the K-θ -h relations may be partly based on an assumption that its effects are negligible, partly on the absence of a well-validated hysteretic model that is easy to calibrate (Lenhard et al, 1991), and partly on the difficulties of performing measurement experiments that are suitable to identify parameters of hysteresis models. Neglecting hysteresis leads to significant errors in the water redistribution under transient boundary conditions (Dane and Wierenga, 1975;Gillham et al, 1979, Hoa et al, 1977Viaene et al, 1994;Lehmann et al, 1999;Si and Kachanoski, 2000). Russo et al (1989) and Mitchell and Mayer (1998) investigated the influence of hysteresis on solute transport and found that the magnitude of the deviations between hysteretic and nonhysteretic simulations was not a simple function of single parameters, but rather depended on the combined values of many or all of the hydraulic parameters.…”
Section: Hysteresismentioning
confidence: 99%